Implementation of cryogenic tender X‐ray HR‐XANES spectroscopy at the ACT station of the CAT‐ACT beamline at the KIT Light Source. (23rd December 2021) - Schacherl, Bianca; Prüssmann, Tim; Dardenne, Kathy; Hardock, Kirsten; Krepper, Volker; Rothe, Jörg; Vitova, Tonya; Geckeis, Horst
Abstract : The capabilities for the investigation of radionuclide materials by high‐resolution X‐ray emission spectroscopy techniques at the CAT‐ACT beamline of the Karlsruhe Institute of Technology (KIT) Light Source have been expanded to allow for the investigation of redox‐labile low‐concentration samples at cryogenic temperatures. Abstract : The ACT experimental station of the CAT‐ACT wiggler beamline at the Karlsruhe Institute of Technology (KIT) Light Source is dedicated to the investigation of radionuclide materials with radioactivities up to 1000000 times the exemption limit by various speciation techniques applying monochromatic X‐rays. In this article, the latest technological developments at the ACT station that enable high‐resolution X‐ray absorption near‐edge structure (HR‐XANES) spectroscopy for low radionuclide loading samples are highlighted – encompassing the investigation of actinide elements down to 1 p.p.m. concentration – combined with a cryogenic sample environment reducing beam‐induced sample alterations. One important part of this development is a versatile gas tight plexiglass encasement ensuring that all beam paths in the five‐analyzer‐crystal Johann‐type X‐ray emission spectrometer run within He atmosphere. The setup enables the easy exchange between different experiments (conventional X‐ray absorption fine structure, HR‐XANES, high‐energy or wide‐angle X‐ray scattering, tender to hard X‐ray spectroscopy) and opens up the possibility for the investigation of environmental samples, such as specimens containing transuranium elements from contaminated land sites or samples from sorption and diffusion experiments to mimic the far field of a breached nuclear waste repository.